Silencing of A20 Aggravates Neuronal Death and Inflammation After Traumatic Brain Injury: A Potential Trigger of Necroptosis - Bao, Zhongyuan; Fan, Liang; Zhao, Lin; Xu, Xiupeng; Liu, Yinlong; Chao, Honglu; Liu, Ning; You, Yongping; Liu, Yan; Wang, Xiaoming; Ji, Jing (Frontiers in Molecular Neuroscience, 2019)
Programmed cell death is an important biological process that plays an indispensable role in traumatic brain injury (TBI). Inhibition of necroptosis, a type of programmed cell death, is pivotal in neuroprotection and in preventing associated inflammatory responses. Our results showed that necroptosis occurred in human brain tissues after TBI. Necroptosis was also induced by controlled cortical impact (CCI) injury in a rat model of TBI and was accompanied by high translocation of high-mobility group box-1 (HMGB1) to the cytoplasm. HMGB1 was then passed through the impaired cell membrane to upregulate the receptor for advanced glycation end-products (RAGE), nuclear factor (NF)-κB, and inflammatory factors such as interleukin-6 (IL-6), interleukin-1 (IL-1β), as well as NACHT, LRR and PYD domains-containing protein 3 (NLRP3). Necroptosis was alleviated by necrostatin-1 and melatonin but not Z-VAD (a caspase inhibitor), which is consistent with the characteristic of caspase-independent signaling. This study also demonstrated that tumor necrosis factor, alpha-induced protein 3 (TNFAIP3, also known as A20) was indispensable for regulating and controlling necroptosis and inflammation after CCI. We found that a lack of A20 in a CCI model led to aggressive necroptosis and attenuated the anti-necroptotic effects of necrostatin-1 and melatonin.